PEWARISAN PERMAINAN TRADISIONAL PADA ANAK USIA DINI SEBAGAI SARANA REKREATIF, KOMPETITIF DAN EDUKATIF - mustakim mustakim (JIEEC (Journal of Islamic Education for Early Childhood), 2021)
Culture as a community heritage handed down from generation to generation. Inheritance of character values in children becoming a fundamental requirement for the foundation of a child to adulthood. Traditional games as a legacy of the archipelago are starting to fade among the melenial generation, the flow of digital technology is the main factor in traditional games being abandoned. Children are more love to play the gadget, online games, internet, social media, ticktock, and youtube. Melenial generation began not familiar with the heritage of traditional games developed in the community. The purpose of this study to describe the concept of inheritance of traditional games in early childhood. The method used qualitative methods using the technique of interview, observation and documentation. The results of the study illustrate that traditional games provide recreational, competitive, and educational values for early childhood, as a means of physical motor development for children.